2020
DOI: 10.1111/pcmr.12878
|View full text |Cite
|
Sign up to set email alerts
|

The enigma and challenges of vitiligo pathophysiology and treatment

Abstract: Vitiligo is an acquired pigmentary disorder characterized by sharply demarcated, variably shaped depigmented macules and patches that appear commonly, but not exclusively, on the face, dorsa of the hands, nipples, axillae, umbilicus, and sacral, inguinal, and anogenital regions, surrounded by normal skin (Ezzedine, Eleftheriadou, Whitton, & Geel, 2015). Vitiligo can be broadly classified into two major forms, non-segmental and segmental vitiligo (Figure 1). This classification is based in part on the distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 115 publications
0
60
0
Order By: Relevance
“…Vitiligo is considered to be an autoimmune disease because cytokines such as (IFN)-γ, IL-1, IL-6, IL-8, and IL-10 are overexpressed in lesions, and activated CD8 + T lymphocytes, TH17, and other immune cells are significantly aggregated in the lesion area (16)(17)(18)(19). However, some researchers have suggested that autoimmunity may be secondary to high oxidative stress in vitiligo skin, leading to inherent defects of melanocytes and changes in its microenvironment (4). At present, the unified view is that the inherent defect of melanocytes is an early event in vitiligo, and the gradual disappearance of epidermal melanocytes leads to skin depigmentation of vitiligo lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitiligo is considered to be an autoimmune disease because cytokines such as (IFN)-γ, IL-1, IL-6, IL-8, and IL-10 are overexpressed in lesions, and activated CD8 + T lymphocytes, TH17, and other immune cells are significantly aggregated in the lesion area (16)(17)(18)(19). However, some researchers have suggested that autoimmunity may be secondary to high oxidative stress in vitiligo skin, leading to inherent defects of melanocytes and changes in its microenvironment (4). At present, the unified view is that the inherent defect of melanocytes is an early event in vitiligo, and the gradual disappearance of epidermal melanocytes leads to skin depigmentation of vitiligo lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of vitiligo manifests as oxidative stress, infiltration of inflammatory mediators, melanocyte loss, and autoimmune responses (3). It is caused due to the complex interaction among environmental and genetic factors that eventually leads to melanocyte dysfunction (4). However, the inherent defect in melanocytes is an early event in vitiligo; the gradual disappearance of melanocytes may involve multiple processes, including immune system attack, cell degeneration, and exfoliation among others (1).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is the most common depigmenting skin disorder which affects approximately 0.5-1% of the population across the world. 2 Vitiligo has a serious negative influence on patients' self-esteem and confidence; it often occurs at exposed sites such as the face, 1 which seriously affects patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Melanin metabolic abnormalities play a crucial role in the development of vitiligo. 2,3 Abnormal melanin loss leads to vitiligo associated pathological processes. 4 Therefore, therapies that promote melanogenesis and melanocyte proliferation have been considered as the most promising treatment methods for vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…Vitiligo is a pigmentary disorder that results in depigmented patches due to melanocyte loss (Abdel‐Malek et al., 2020). There are two forms of vitiligo: segmental and non‐segmental vitiligo.…”
Section: The Upr/isr In Disease Pathologymentioning
confidence: 99%